Analisis Dongeng Cinderella Melalui Perspektif Filsafat Progresivisme: Membangun Kreativitas dan Kritis dalam Pendidikan Berbasis Pengalaman - Sri Wahyuni, Sri Wahyuni; Syihabuddin, Syihabuddin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Abstract: This research analyzes the Cinderella story through the perspective of progressivism philosophy initiated by John Dewey, which emphasizes the importance of direct experience and developing critical thinking skills and creativity in the educational process. The aim of this research is to explore and examine the values contained in the Cinderella story that can be used in progressive education. The research method used is a qualitative descriptive method, where data is obtained from analysis of the text of the Cinderella story. This analysis focuses on story elements that are relevant to the concept of progressivism, such as Cinderella's life experiences, problem solving, and the learning process faced by the main character. This data is then connected to progressive education theory to show the relevance of this story in the context of modern learning. The research results show that the Cinderella story has many aspects that can be linked to the principles of progressivism. This story provides many examples of experiences that are relevant to real life, such as perseverance in facing challenges and the ability to adapt in difficult situations. These values are very important in developing students' critical thinking skills and creativity, especially in experience-oriented education. The story of Cinderella can be used as an effective educational tool in experience-based learning, in accordance with the principles of progressivism philosophy.